2022
DOI: 10.1186/s12866-022-02570-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, discrimination, and molecular detection of Listeria species from slaughtered cattle in Namwala District, Zambia

Abstract: Background The food industry is increasingly becoming more scrutinized, given the frequency and intensity with which zoonotic diseases are being reported. Pathogen tracking has become more applicable with regards food safety. It is in this regard that the present study was formulated to track Listeria species. in freshly slaughtered cattle carcasses by utilizing standard and molecular biological techniques. Methods A cross-sectional study design wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Our findings highlighted the presence of L. monocytogenes mainly in ham and polony; the latter was the same type of product involved in the SA outbreak ( Smith et al, 2019 ). Previous studies conducted in Zambia reported the prevalence of L. monocytogenes in 74% of poultry dressed carcasses ( Mpundu et al, 2022a ) and 26.3% in cattle carcasses ( Mpundu et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlighted the presence of L. monocytogenes mainly in ham and polony; the latter was the same type of product involved in the SA outbreak ( Smith et al, 2019 ). Previous studies conducted in Zambia reported the prevalence of L. monocytogenes in 74% of poultry dressed carcasses ( Mpundu et al, 2022a ) and 26.3% in cattle carcasses ( Mpundu et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to estimate the burden of teenage pregnancies in terms of prevalence and incidence, but this is only one aspect of the problem, as it does not put a ‘face’ to teenage mothers. Economic and socio-cultural factors influence the likelihood of a girl getting pregnant whilst still a teenager, and these may be missed in studies that focus on numbers such as prevalence and incidence (8, 10, 12, 17). Pregnancies occurring during the adolescent years have been associated with interference with the girl’s education.…”
Section: Introductionmentioning
confidence: 99%
“…L. monocytogenes is commonly isolated from animal hosts (cattle, sheep and birds) [7][8][9][10] and their food products (raw meat, pasteurized milk, fish) [11][12][13], as well as environmental sources, such as soil, vegetables, sewage and other water sources [14][15][16][17][18]. Consumption of any of these food sources can lead to infection of the host via translocation of the intestinal barrier, infection of the lymph nodes, and the pathogen subsequently entering the spleen and liver [19].…”
Section: Introductionmentioning
confidence: 99%